Mechanisms of Hydromorphone-Mediated Protection Against Myocardial Ischemia-Reperfusion Injury via NLRP3 Inflammasome Inhibition - Zeng S; Xu W; Ren F; Xiong Q; Qing Q; Luo L; Song X; Tan Y; Huang Z; Zheng M (Journal of Inflammation Research)
Shiyue Zeng,1,2 Wei Xu,2 Fangyuan Ren,3 Qiangqiang Xiong,2 Qi Qing,1 Liu Luo,2 Xi Song,2 Yurong Tan,4 Zhujun Huang,2 Mingzhi Zheng2 1Department of Anesthesiology, Zhuzhou Clinical College, Jishou University, Zhuzhou, Hunan Province, People’s Republic of China; 2Department of Anesthesiology, Zhuzhou Central Hospital, Zhuzhou, Hunan Province, People’s Republic of China; 3Department of Obstetrics, Zhuzhou Central Hospital, Zhuzhou, Hunan Province, People’s Republic of China; 4Department of Medical Microbiology, Central South University Changsha, Changsha, Hunan Province, People’s Republic of ChinaCorrespondence: Zhujun Huang, Department of Anesthesiology, Zhuzhou Clinical College, Jishou University, Zhuzhou, 412000, People’s Republic of China, Tel +8613973320858, Email 1030844526@qq.com Mingzhi Zheng, Department of Anesthesiology, Zhuzhou Clinical College, Jishou University, Zhuzhou, 412000, People’s Republic of China, Tel +8613874195026, Email 547135294@qq.comBackground: Myocardial ischaemia/reperfusion, MI/R injury causes significant cardiac damage, leading to disability and mortality. Although hydromorphone attenuates MI/R injury in rat models, its underlying mechanisms remain unclear.Objective: This study aimed to investigate the protective effects of hydromorphone against MI/R injury and elucidate its mechanisms.Methods: A rat MIRI model was established by occluding the left coronary artery for 30 minutes followed by reperfusion for 120 minutes. Infarct size and cardiac function were assessed using hematoxylin-eosin, HE and Masson’s staining. An in vitro model was established using H9C2 cells subjected to hypoxia/reoxygenation, and levels of cellular pyroptosis and pyroptosis-related proteins were quantified.Results: Hydromorphone significantly improved cardiac function in MIRI rats. Pre- and post-treatment with hydromorphone significantly improved cardiomyocyte morphology in MIRI rats. In addition, compared with the model group (IR), the hydromorphone-treated groups (HH+IR, IR+HH) significantly reduced the rna expression of NLRP3, ASC, caspase-1, IL-1β, and IL-18, as well as the protein levels of IL-1β, IL-18. In addition, transmission electron microscopy showed that hydromorphone attenuated CoCl2-induced cardiomyocyte injury.Conclusion: Pre- or post-treatment with hydromorphone exerts protective effects against MIRI by suppressing NLRP3 inflammasomes, potentially providing a theoretical basis for its use as a therapeutic agent in MIRI patients.Keywords: myocardial ischaemia/reperfusion, MI/R injury, hydromorphone, hypoxia/reoxygenation, NLRP3 inflammatory vesicles